The role of traditional knowledge and food biodiversity to transform modern food systems. (December 2022) - Kennedy, Gina; Wang, Zeyuan; Maundu, Patrick; Hunter, Danny
Abstract: Background: The current way our food systems operate does not result in healthy and nutritious diets for all, nor are we producing food in a manner that the planet can sustain. Food biodiversity, or the range of animal and plant species used for food is one solution to improve the health of both people and the planet. Scope/approach: Case studies were used to illustrate current initiatives and programs aimed to bring greater food biodiversity into our food systems. Case studies were developed by subject matter experts and reviewed for demonstrated and potential impact on four food system outcomes: healthy diets and nutrition, agro-ecological resilience, livelihoods and income and socio-cultural wellbeing. Key findings/conclusion: The six case study examples demonstrate that there are multiple approaches that confer benefits across a range of food system outcomes. The case studies demonstrate contributions to the body of knowledge on food composition, dietary diversification, strategies to prioritize crops that regenerate soil and purify water, require few inputs or can grow in harsh conditions, as well as provide increased income to communities and rebuild cultural knowledge. Some approaches were initiated by government and others at community level; they all demonstrate ways to achieve greater integration of food biodiversity into food systems. This collection of case studies illustrates a fraction of what is currently being done to support biodiverse food production and consumption. The evidence base for how to bring greater food biodiversity back into our food systems should be improved and should not be an isolated occurrence, but rather a continuous process. Highlights: A collection of case studies was used to illustrate current initiatives and programs aimed to bring greater food biodiversity into our food systems. The case studies demonstrate contributions to the body of knowledge on nutrition, through food composition data and dietary diversification strategies. Contributions to agro-ecology are demonstrated through strategies to prioritize crops that regenerate soil and purify water, require few inputs or can grow in harsh conditions. Income generation through greater use of food biodiversity was demonstrated in two case studies. Many of the case studies provided evidence of benefit to socio-cultural wellbeing.